Tree species composition and above ground biomass of a 15-year-old logged-over forest at Pasoh, Negeri Sembilan, Peninsular Malaysia - Hanum, I.F.; Norhisyam, T.M.; Sabri, M.; Azani, A.M.; Mokhtaruddin, A.M.; Maswar; Yusoff, M.K.; Majid, N.M.; Kobayashi, S. (Center for International Forestry Research, 2001)
From a study conducted in Pasoh Forest Reserve, 149 tree species in 92 genera and 38 families, all trees with a diameter breast height (dbh) of 1 cm or above were enumerated in a one hectare plot. The most abundant species was Ficus fistulosa across all dbh classes followed by Monocarpia marginalis and Dipterocarpus cornutus. The most diverse family was Euphorbiaceae with 25 species followed by Dipterocarpaceae (13 spp.) and Leguminosae (13 spp.). Stand density was 1951 stems ha-1 with Euphorbiaceae contributing about one-fifth the total number of stems. High densities of pioneer species such as Macaranga spp., Vitex pinnata and young trees of primary species, such as Dipterocarpus spp. and Shorea spp., indicate that the forest is still in an early stage of succession, yet has recovered rather well from previous disturbances, such as forest harvesting. The estimated above ground biomass was 160.8 t ha-1, a reasonable value for a 15-year-old forest, also suggesting the capability of this forest to recover from previous forest harvesting.